EFISIENSI USAHA PEMBIBITAN ITIK MODERN DAN TRADISIONAL PADA SKALA RUMAH TANGGA DI KABUPATEN LEBONG - Anwar, Nuril; Utama, Satria Putra; Reswita, Reswita (Jurnal AGRISEP, 2015)
The objectives of this research are to determine the income level and to estimate the differencies of income between modern and traditional techniques of breeding by the household in Amen and Lebong Sakti subdistrict, Lebong District. The determination of the amount of revenue is done using analysis of revenues, while for testing whether there are differences in the income of both the duck breeding efforts carried out by different assay analysis of average income. The calculation to determine the level of efficiency of the business activities of breeding ducks using R/C ratio. Based on the results of the research the average revenues of modern ducks nursery is Rp. 1.331.969,21 for four months, while the average income of the traditional duck breeding attempt amounted to Rp. 1.662.396,66 for four months. After a test of the difference of income between enterprises of modern and traditional duck breeding, breeding of modern ducks revenues smaller revenues equal to the traditional duck breeding where the real differences in the degrees of confidence 95. The average value of the results analysis of R/C ratio in modern duck breeding efforts Lebong is equal to 2.00 while R/C ratio of the traditional duck breeding amounted to 2.15.